Experiencia de padres al cuidado de sus hijos post terapia ECMO en su domicilio (2024)
Extracorporeal membrane oxygenation (ECMO) is a type of support intended for short-term blood flow support managed in neonates, children and adults with severe cardiopulmonary failure. This therapy is used to help patients with acute as well as chronic circulatory disorders or post-cardiotomy complexity, including intractable arrhythmias, cardiac arrest and severe respiratory failure. For this reason it is of great importance to know the clinical history of the pediatric patient before starting treatment, especially cardiorespiratory pathologies, in addition to this, pediatric patients require specific stimulation care for development and effective strengthening, respiratory care, among others. Considering the above, it is important to understand the experiences of parents with children who have undergone ECMO therapy for different pathologies.